STRATEGI INOVATIF PEMASARAN PRODUK ES BUAH UNTUK MENINGKATKAN PENJUALAN DI PASAR NITA KECAMATAN NITA KABUPATEN SIKKA - Sarlina Noni; Benedikta Yuliana Loru; Efrensius Koli Ndane; Ignasius Umbu Pati; Rikeldis Mula Toka Onacha (Universitas Cokroaminoto Palopo, 2025)
This study aims to identify the innovative marketing strategies employed by fruit ice vendors in efforts to increase sales at Nita Market, Nita District, Sikka Regency. The background of this research is based on the increasingly fierce competition among vendors, requiring more creative marketing strategies to attract customers. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation of several fruit ice vendors at Nita Market. The results show that vendors implement several innovative marketing strategies, such as offering a variety of fruit ice menus, using more attractive packaging, providing fast and friendly service, offering affordable prices, and conducting simple promotions via social media platforms like WhatsApp and Facebook. Additionally, maintaining cleanliness of the stalls and using fresh ingredients are important factors that build consumertrust and interest. In conclusion, the innovative marketing strategies applied by fruit ice vendors at Nita Market have proven effective in increasing the number of buyers and revenue. This research is expected to serve as a reference for other vendors to develop their businesses through more creative marketing strategies tailored to market needs